Le jeu des qualifications juridiques au service de l’évitement du droit pénal - Isabelle Fouchard (Criminocorpus)
This contribution explores the issues of legal qualification in the prosecution and judgment of crimes committed by members of the French armed forces during the Algerian war of independence and the way in which the Court of Cassation refused to retain the qualification of crime against humanity in this context to justify the incompetence of the French courts with regard to these crimes.